1998
DOI: 10.1002/mrm.1910390503
|View full text |Cite
|
Sign up to set email alerts
|

Blood oxygen saturation assessment in vivo using T2 * estimation

Abstract: The feasibility of noninvasively assessing hemoglobin oxygen saturation of deep blood vessels in vivo by measuring blood T2* is investigated. Techniques for blood T2* measurements in major arteries and veins in the presence of pulsatile blood flow are presented and validated using a flow phantom. Images of multiple TEs were collected in a paired fashion. Cardiac triggering was used to eliminate image artifacts caused by pulsatile arterial blood flow. Using these techniques, it was found that the T2* of arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 17 publications
(25 reference statements)
5
75
2
Order By: Relevance
“…These values are slightly different from those given in Ref. 10 and contain the experimental results of Li et al (29) for the T* 2 values of blood at 1.5T in dependence of the oxygenation. In Ref.…”
Section: Appendixcontrasting
confidence: 97%
“…These values are slightly different from those given in Ref. 10 and contain the experimental results of Li et al (29) for the T* 2 values of blood at 1.5T in dependence of the oxygenation. In Ref.…”
Section: Appendixcontrasting
confidence: 97%
“…11 The locally increased ratio of deoxyhaemoglobin to oxyhaemoglobin in cortical and medullary veins might be an expression of ischaemia and represent the degree of hypoperfusion and oxygen extraction. 20,21 Several studies have indeed shown an association between T 2 * signal drop and increased oxygen extraction fraction. 20,21 Since the oxygen extraction fraction is increased in the ischaemic penumbra, some authors suggested that prominent hypointense veins on SWI could possibly represent the penumbra.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Several studies have indeed shown an association between T 2 * signal drop and increased oxygen extraction fraction. 20,21 Since the oxygen extraction fraction is increased in the ischaemic penumbra, some authors suggested that prominent hypointense veins on SWI could possibly represent the penumbra. 4,7 Such a penumbra may diminish, as reperfusion is achieved via intervention, or a new perfusion balance is achieved through collateral veins.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (44) have also estimated human blood R* 2 as a function of oxygenation level with a gradient-echo sequence. Although the sample Hct is not reported in their study, the exponential relaxation rate constant, R* 2 , that they report for fully oxygenated blood seems to be somewhat large at 7.2 sec -1 for a blood sample with normal Hct level.…”
Section: Discussionmentioning
confidence: 99%